2015
DOI: 10.1002/aur.1523
|View full text |Cite
|
Sign up to set email alerts
|

Autistic Traits Moderate the Impact of Reward Learning on Social Behaviour

Abstract: A deficit in empathy has been suggested to underlie social behavioural atypicalities in autism. A parallel theoretical account proposes that reduced social motivation (i.e., low responsivity to social rewards) can account for the said atypicalities. Recent evidence suggests that autistic traits modulate the link between reward and proxy metrics related to empathy. Using an evaluative conditioning paradigm to associate high and low rewards with faces, a previous study has shown that individuals high in autistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 48 publications
1
18
0
Order By: Relevance
“…Crucially, this reward-dependent modulation of spontaneous smile mimicry was inversely related to autistic traits (i.e., individuals high in autistic traits showed little facilitation of spontaneous mimicry for high versus low rewarding faces). An extension of these findings, using the same evaluative conditioning paradigm, showed that autistic traits did not moderate the extent of (implicit) conditioning (as measured by an implicit association test), but did reduce subsequent prosocial behavior toward the conditioned high-reward identities (Panasiti et al 2016). This is especially interesting in the context of previous reports linking mimicry and prosocial behavior (van Baaren et al 2004).…”
Section: Individual Differences: Oxytocin and Reward Processingmentioning
confidence: 51%
“…Crucially, this reward-dependent modulation of spontaneous smile mimicry was inversely related to autistic traits (i.e., individuals high in autistic traits showed little facilitation of spontaneous mimicry for high versus low rewarding faces). An extension of these findings, using the same evaluative conditioning paradigm, showed that autistic traits did not moderate the extent of (implicit) conditioning (as measured by an implicit association test), but did reduce subsequent prosocial behavior toward the conditioned high-reward identities (Panasiti et al 2016). This is especially interesting in the context of previous reports linking mimicry and prosocial behavior (van Baaren et al 2004).…”
Section: Individual Differences: Oxytocin and Reward Processingmentioning
confidence: 51%
“…As expected, participants made fewer egoistic lies to high than low‐warmth individuals, supporting the idea that moral information is of primary importance in guiding social judgements and interpersonal behaviour (Brambilla, Rusconi, Sacchi, & Cherubini, ; Delgado et al ., ; Liuzza, Candidi, Sforza, & Aglioti, ; Mancini, Betti, Panasiti, Pavone, & Aglioti, ; Panasiti, Puzzo, & Chakrabarti, ; Willis & Todorov, ; Wojciszke et al ., ). These results expand previous evidence that people tend to trust (Delgado et al ., ) and cooperate (Steinel & De Dreu, ) more with warm individuals, by showing that inferred warmth reduces the tendency to deceive others.…”
Section: Discussionmentioning
confidence: 97%
“…These include abnormal behavioral responses when processing social stimuli (Sepeta et al, 2012; Yeung, Han, Sze, & Chan, 2014), such as atypical activation of reward circuitry during the anticipation and processing of monetary incentives and social cues (Dichter et al, 2012; Ingersoll, Schreibman, & Tran, 2003; Panasiti, Puzzo, & Chakrabarti, 2015; Rademacher, Schulte-Ruther, Hanewald, & Lammertz, 2016). Studies using a variety of methods suggest that ASD is characterized, in part, by atypical engagement of frontal and striatal systems (Glerean et al, 2016; Langen et al, 2014).…”
Section: Introductionmentioning
confidence: 99%